Lower ionospheric electron density changes following lightning discharges - Atici, Ramazan; Guzel, Esat; Sagir, Selcuk (Springer Int Publ Ag, 2018)
The effect of lightning-induced electromagnetic (EM) waves on electron density (N-e) of the lower ionosphere is calculated by using the four-component Glukhov-Pasko-Inan (GPI) model which is modified by including two-body attachment reactions and associative detachment with negative ions of active species (namely, O and N atoms). As a result of the calculations, it is seen that three-body attachment reactions take place at about 50-73 km altitudes, associative detachment takes place at approximately 73-85 km altitudes and two-body attachment reactions take place at approximately 85-95 km altitudes on the electron density. While the effect on electron density of electric field of lightning-induced EM wave is weak at altitudes where associative detachment is effective, it is strong at altitudes where two-body attachment reactions are effective. Also, it is shown that the electron density increases up to approximately 5.5 times when compared with the background density values due to electrons occurring as a result of associative detachment with negative ions of active species.
Keywords: Lower ionosphere; Electron density; Lightning-induced EM waves; GPI model